Normal positive electrical circuits - Kaczorek, Tadeusz (IET control theory & applications, 2015)
A new notion of normal positive electrical circuits is proposed. It is shown that any positive second-order electrical circuit with 2-inputs and 2-outputs is normal and a positive electrical circuit with m-inputs and p-outputs (m, p ≥ 2) is normal if its system matrix A has distinct eigenvalues or its system matrix is symmetric.